Intramuscular Injection of Bone Marrow Stem Cells in Amyotrophic Lateral Sclerosis Patients: A Randomized Clinical Trial - Geijo-Barrientos, Emilio; Pastore-Olmedo, Carlos; De Mingo, Pedro; Blanquer, Miguel; Gómez Espuch, Joaquín; Iniesta, Francisca; Iniesta, Natalia García; García-Hernández, Ana; Martín-Estefanía, Carlos; Barrios, Laura; Moraleda, José M.; Martínez, Salvador (Frontiers in Neuroscience, 2020)
Background. Preclinical studies suggest that stem cells may be a valuable therapeutic tool in amyotrophic lateral sclerosis (ALS). As it has been demonstrated that there are molecular changes at the end-plate during the early stages of motorneuron degeneration in animal models we hypothesize that the local effect of this stem cell delivery method could slow the progressive loss of motor units (MU) in ALS patients. Methods. We designed a Phase I/II clinical trial to study the safety of intramuscularly implanting autologous bone-marrow mononuclear cells (BMMCs), including stem cells, in ALS patients and their possible effects on the MU of the tibialis anterior (TA) muscle. Twenty-two patients participated in a randomized, double-blind, placebo-controlled trial that consisted of a baseline visit followed by one intramuscular injection of BMNCs, follow-up visits at 30, 90, 180 and 360 days, and an additional year of clinical follow-up. In each patient, one TA muscle was injected with a single dose of BMMCs while the contralateral muscle was given a placebo; the sides were selected randomly. All visits included a complete EMG study of both TA muscles. Results. Our results show that: 1) the intramuscular injection of BMMCs is a safe procedure; 2) ALS patients show heterogeneities in the degree of TA injury; 3) a comparison of placebo-injected with BMMC-injected muscles showed significant differences in only one parameter, the D50 index used to quantify the Compound Muscle Action Potential (CMAP) scan curve. This parameter was higher in the BMMC-injected TA muscle at both 90 days (placebo side: 29.55±2.89, n=20; experimental side: 39.25±3.21, n=20; p<0.01) and 180 days (placebo side: 29.35±3.29, n=17; experimental side: 41.24±3.34, n=17; p<0.01). Conclusions. This procedure had no effect on the TA muscle MU properties, with the exception of the D50 index. Finding differences in just this index supports the fact that it may be much more sensitive than other electrophysiological parameters when studying treatment effects. Given the low number of patient and their heterogeneity, these results justify exploring the efficacy of this procedure in further patients and other muscles, through phase II trials. Clinical Trial Registration www.clinicaltrials.gov (identifier NCT02286011); EudraCT number 2011-004801-25.